Abuse and neglect of children in Macedonia: present situation and future challenges - Jordanova Peshevska , Dimitrinka; Tozija , Fimka (Ревија за социјална политика/Journal of Social Policy, 2017)
The prevention and protection of children from violence is a fundamental right of every child. However, violence remains a severe reality for millions of children, having lifelong consequences on children`s life span and development. The main objective of the paper is to describe the burden of child abuse and neglect, risk factors in Republic of Macedonia and discuss the need for national policy and legal framework reinforcement. The World Health Organization`s Global Health Estimates data were used to describe the burden and mortality of child abuse and neglect, and literature review and analyses of previous reports were used to describe the prevalence of the different types of child abuse and neglect in Republic of Macedonia and discuss the options for national policy, as well as legal framework reinforcement. The World Health Organization`s European Region of 53 states data, indicated that 55 million children (29.1%) are victims of emotional abuse, 44 million (22.9%) of physical abuse, victims of physical neglect are 31 million (16.3%), and 18 million (9.6%) children victims of sexual abuse. According to the research data, in Macedonia more than one fifth (21%) of all students have been exposed to various forms of physical abuse during childhood. More than 30% of the respondents-adolescents have been exposed to some form of psychological neglect; 11% to psychological abuse, and 13% to some kind of sexual abuse. The problem of child abuse and neglect in Macedonia, in comparison with other countries from the South East European Region, has undergone important milestones for improvement in prevention and protection of children from violence. However, there is an opportunity for improvement in reinforcing the national policies and legal framework, as well as implementing evidence based preventive programmes, since the findings are still confronting very high figures of prevalence of child abuse and neglect.
Keywords: abuse; neglect; child; burden; preventive measures; national policies